2013
DOI: 10.1590/0004-282x20130007
|View full text |Cite
|
Sign up to set email alerts
|

Programmable valve represents an efficient and safe tool in the treatment of idiopathic normal-pressure hydrocephalus patients

Abstract: Idiopathic normal pressure hydrocephalus (iNPH) is a condition characterized by gait disturbance, dementia and/or urinary incontinence without causative disorders, as well as dilation of ventricular system due to disturbance of cerebrospinal fluid (CSF) circulation with normal CSF pressure and no secondary cause [1][2][3] . It is a differential diagnosis for most of the dementia syndromes and occurs mainly in elderly populations 4 .The known incidence is approximately 6 per 100,000 and it has a prevalence of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
46
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 31 publications
2
46
0
1
Order By: Relevance
“…Pacientes com HPN podem desenvolver sintomas com predomínio frontal, tais como mudanças de personalidade, ansiedade, depressão, síndromes psicóticas, transtorno obsessivo compulsivo, síndrome de Otelo, furtos e mania. Sintomas incomuns de HPN podem dificultar o diagnóstico precoce e o tratamento adequado.Palavras-chave: hidrocefalia de pressão normal, sintomas, psiquiatria.Normal pressure hydrocephalus (NPH) is a syndrome characterized by gait disturbance, dementia and urinary incontinence plus dilation of ventricular system due to disturbance of cerebrospinal fluid (CSF) circulation with normal CSF pressure 1,2,3,4,5,6 . Dilated ventricles theoretically impair perfusion in ventricular walls, generating hypoperfusional states especially in frontal lobes, basal ganglia and thalamus, thus resulting classic symptomatology 7 .…”
unclassified
See 1 more Smart Citation
“…Pacientes com HPN podem desenvolver sintomas com predomínio frontal, tais como mudanças de personalidade, ansiedade, depressão, síndromes psicóticas, transtorno obsessivo compulsivo, síndrome de Otelo, furtos e mania. Sintomas incomuns de HPN podem dificultar o diagnóstico precoce e o tratamento adequado.Palavras-chave: hidrocefalia de pressão normal, sintomas, psiquiatria.Normal pressure hydrocephalus (NPH) is a syndrome characterized by gait disturbance, dementia and urinary incontinence plus dilation of ventricular system due to disturbance of cerebrospinal fluid (CSF) circulation with normal CSF pressure 1,2,3,4,5,6 . Dilated ventricles theoretically impair perfusion in ventricular walls, generating hypoperfusional states especially in frontal lobes, basal ganglia and thalamus, thus resulting classic symptomatology 7 .…”
unclassified
“…NPH can present in two forms: primary (also known as idiopathic), when there are no causative disorders and secondary, where other disorders such as trauma, infection and hemorrhage are putative causes for hydrocephalus 1,2,3,4,5,6 . Idiopathic NPH (INPH) is associated with communicating hydrocephalus (as demonstrated by brain CT or MRI) and CSF pressure within normal range (7-24 cm H2O) 1,2,3,4,5,6 . With improvements in quality of life and subsequent increase in life expectancy, it is expected that a greater number of elderly individuals will suffer from this disease.…”
mentioning
confidence: 99%
“…Oliveira et al showed that up to 70% of patients with NPH may present neuropsychiatric symptoms, which may be from metabolic impairments in frontal lobe, basal ganglia and thalamus, all of which can be involved in pathophysiology of OS [1][2][3][4][5][6][7][8][9][10] .…”
Section: Discussionmentioning
confidence: 99%
“…Dear Editor, Normal pressure hydrocephalus (NPH) is a syndrome characterized by urinary incontinence, gait disturbance and dementia plus dilation of ventricular system due to disturbance of cerebrospinal fluid (CSF) circulation [1][2][3][4] . There is wide scientifical evidence pointing association between NPH and psychiatric symptoms [1][2][3][4] .…”
mentioning
confidence: 99%
See 1 more Smart Citation